663 Electronic Microscopy aspects of experimentally induced chronic arthritis (Balneo and PRM Research Journal, 2024)
: Chronic diseases are responsible for about 38 million deaths annually and represent about 70% of all deaths worldwide. Among these, rheumatoid arthritis is the most common inflammatory rheumatic dis-ease, representing about 10% of all such disorders. Its incidence is approximately 1% of the general popula-tion.Material and method: our study aims to create an experimental model of chronic arthritis on Wistar rats, fe-male sex, to follow the dynamics of joint inflammatory phenomena, the effects of Leflunomide in their evolu-tion and the side effects at cardiac, hepatic and renal level.Discussions: The group of young experimental animals developed more extensive inflammatory phenomena compared to the group of adult animals. Leflunomide did not significantly improve the evolution and resolu-tion of inflammatory phenomena in either group.Conclusions: We showed for the first time in the world the effects of Leflunomide on the heart, with the occur-rence of myocardial necrosis ( myocardial infarction) as its main adverse effect.Keywords: Arthritis, Leflunomide